2021
DOI: 10.1021/acsami.1c19404
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Mode Circularly Polarized Light Emission and Metal-Enhanced Fluorescence Realized by the Luminophore–Chiral Cellulose Nanocrystal Interfaces

Abstract: Circularly polarized (CP) light has attracted wide attention for its great potential in broad applications. However, it remains a challenge to generate left-handed and right-handed circularly polarized (LCP and RCP) light from cellulose nanocrystal (CNC)-based materials only with an intrinsic left-handed chiral structure, owing to the pattern of CP light emission primarily based on the chirality of materials. Herein, a separation structure of luminophore layers and chiral CNCs was provided to achieve dualmode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Cellulose nanocrystals (CNCs), due to their intriguing hierarchical chirality, especially that derived from self-assembled cholesteric structures, are considered as powerful chiral nanomaterials to manufacture CPL-active platform. [43,[147][148][149][150][151][152][153] The hydroxyl and charged groups on the CNCs surface can form non-covalent bonds with achiral luminophores, such as organic luminophores, [16,149,[154][155][156][157] quantum dots, [158][159][160] carbon dots (CDs), [161][162][163][164][165] upconverting nanoparticles, [166] and so on. [167,168] The CPL performance of CNCs-based materials is summarized in Table 3.…”
Section: Chiral Component and Luminescent Component: Non-covalent Int...mentioning
confidence: 99%
“…Cellulose nanocrystals (CNCs), due to their intriguing hierarchical chirality, especially that derived from self-assembled cholesteric structures, are considered as powerful chiral nanomaterials to manufacture CPL-active platform. [43,[147][148][149][150][151][152][153] The hydroxyl and charged groups on the CNCs surface can form non-covalent bonds with achiral luminophores, such as organic luminophores, [16,149,[154][155][156][157] quantum dots, [158][159][160] carbon dots (CDs), [161][162][163][164][165] upconverting nanoparticles, [166] and so on. [167,168] The CPL performance of CNCs-based materials is summarized in Table 3.…”
Section: Chiral Component and Luminescent Component: Non-covalent Int...mentioning
confidence: 99%
“…Recently, there has been an increased focus on CNC-based CPL materials in which CNC acts as a chiral template to load achiral guest molecules, yielding strong CPL. [174][175][176][177][178] Due to the intrinsic left-handed chiral nematic structure of CNC films, right-handed CPL (RCPL) is detected. It has been reported that the CPL wavelength and intensity are related to the coupling between the luminescence and photonic bandgap.…”
Section: Responsive Luminescence and Cp Luminescencementioning
confidence: 99%
“…Left-and right-handed CPL emission can be realized by directly exciting the back and front of the bilayer film. [126] NPs have good physical and chemical properties and rich emission spectra because of their unique 4 f-4 f electron transition in the inner shell. [127] Jalilah and coworkers reported that the 4 f-4 f transition in the thin-film state shows CPL after the rare-earth element (Eu III and Tb III ) tris(β-diketonate) complexes intercalate into cellulose triacetate, cellulose acetate butyrate, D-/L-glucose pentamethyl esters, and D-/L-arabinose tetramethyl esters.…”
Section: Cpl Materials Based On Saccharides and Lipidsmentioning
confidence: 99%
“…In another work, they further developed the system and proposed novel dual‐mode CP light‐emitting films with MEF realized by the light emitter–AuTNP/CNC interface. Left‐ and right‐handed CPL emission can be realized by directly exciting the back and front of the bilayer film [126] . NPs have good physical and chemical properties and rich emission spectra because of their unique 4 f–4 f electron transition in the inner shell [127] .…”
Section: Cpl Materials Based On Biomoleculesmentioning
confidence: 99%